Employees Attitudes toward Impacts of Privatization in Saudi Public Sector - Al Qahtani, Noura; Alessa, Ghuzayyil (The Arab Journal of Administration, 2023)
This study aims to reveal the administrative, economic, and social effects of privatization according to the perceptions of workers in the Saudi public sector. Furthermore, it aims to discover whether there are substantial and statistically significant differences in the effects of privatization attributed to personal or functional variables. Data for this study was collected via a questionnaire using the descriptive survey approach. A sample of 532 participants from (8) government agencies in Riyadh, Saudi Arabia were randomly selected. For data processing and analysis, Static Package for Social Science (SPSS) and several appropriate statistical tools were used. Key findings show that administrators in the Saudi public sector recognize the positive effects of privatization on administrative, social, and economic fields. The results also indicate that there are no statistically significant differences in the attitudes of workers in the Saudi public sectors towards the effects of privatization attributable to variables (i.e., age, educational qualification, years of experience), while there are statistically significant differences among the responses of the study participants regarding administrative effects, particularly with respect to not/receiving courses on privatization, with the results being in favour of the courses. According to the findings, the study concludes with several recommendations, including: the importance of providing training courses for employees on privatization, particularly with respect to training type, implications, and effects on trainees. The study also highlights the importance of gradually proceeding with privatization, a process that should include a clear policy that considers, inter alia, those who are rendered unemployed as a consequence thereof.